PARENTAL INVOLVEMENT AND ENGLISH ACHIEVEMENT: INSIGHTS FROM INDONESIAN MIDDLE SCHOOL STUDENTS - Fadlia, Fadlia; Telaumbanua, Siti Pratiwi; Isda, Irma Dewi; Asra, Surya (Universitas Islam Sumatera Utara (UISU), 2025)
Parents play a vital role in supporting their children’s academic achievement. This study aims to identify the types of parental involvement that support students’ English learning at SMPN 3 Langsa and to examine how these forms of involvement relate to students’ English achievement. This study addresses this gap by examining the forms and effects of parental involvement on English achievement among eighth-grade students in an Indonesian public middle school. Guided by Epstein’s Framework of Parental Involvement, this study categorizes parental practices into six types and investigates their relationship with students’ formal English achievement scores. A qualitative-dominant design was employed, triangulating three data sources: (1) questionnaires measuring the frequency of involvement across Epstein’s types, (2) semi-structured interviews exploring parental practices and motivations, and (3) official English score documents quantifying students’ achievement. Findings show that parenting, learning at home, and volunteering were the most frequently practiced types of involvement, with rates of 89%, 84%, and 82%, respectively. Qualitative patterns indicated that learning-at-home involvement—including homework supervision and structured study routines—was strongly associated with higher English achievement scores, particularly among students consistently surpassing the Minimum Mastery Criteria (KKM). The study contributes context-specific evidence for designing targeted parental engagement programs that address the unique demands of L2 learning in Indonesian middle schools.